2023
DOI: 10.1111/jfpe.14296
|View full text |Cite
|
Sign up to set email alerts
|

Drying of peaches by a combination of convective and microwave methods

Abstract: The aim of this work is to study a method to extend the storage life of peaches reducing energy and time consumption and ensuring food quality. The conventional method of hot air dying presents many drawbacks, whereas the microwave drying usually leads to overheating and textural damage. Thus, in this work, a combination of convective and microwave methods, more specifically a two-stage drying process with an initial convective air drying followed by a microwave drying (microwave finishing), was studied for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…In particular, the integration of microwave pretreatment followed by hot air drying has been investigated in several studies on fruit and vegetables. Tese studies have consistently shown that this combined approach results in reduced drying times while maintaining high product quality, characterized by improved visual appeal and reduced nutrient degradation [17,21,30,37,38]. Terefore, the selection of an optimal drying temperature range between 60 and 80 °C was assumed to reduce processing time while maintaining quality attributes.…”
Section: Drying Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the integration of microwave pretreatment followed by hot air drying has been investigated in several studies on fruit and vegetables. Tese studies have consistently shown that this combined approach results in reduced drying times while maintaining high product quality, characterized by improved visual appeal and reduced nutrient degradation [17,21,30,37,38]. Terefore, the selection of an optimal drying temperature range between 60 and 80 °C was assumed to reduce processing time while maintaining quality attributes.…”
Section: Drying Processesmentioning
confidence: 99%
“…Additionally, microwave drying has the advantage of preserving the quality characteristics of the products including color, vitamins, minerals, and nutritional components [16]. However, microwave drying has some undesirable adverse efects due to overheating, thus textural damage on the fnal product can occur [17]. Tose features result in limited application of the method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To preserve the physical, chemical, and sensory properties of peaches, various technologies and drying methods have been employed. Chatzilia et al ( 11 ) and Roknul Azam et al ( 12 ) combined hot-air convection and microwave drying. Pieniazek and Messina ( 13 ) utilized freeze-drying, while Lyu et al ( 14 ) and Zhang et al ( 15 ) initiated the process with osmotic dehydration, followed by infrared pre-drying, and concluded with explosion puffing.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is a trend toward using improved drying methods that are faster, more uniform, hygienic, and require less energy than conventional methods ( 11 , 12 ). However, the selection of a suitable drying technology is a challenging task because fruits and vegetables are susceptible to heating; conductive hydro-drying, such as Refractance Window Drying (RWD), is a novel fourth generation of drying methods with a relatively short processing time, low energy, low cost, scalability, and improved product quality ( 19–22 ).…”
Section: Introductionmentioning
confidence: 99%